Implementasi dan Analisis Performa Pembelajaran Pengenalan Hewan Pada Anak-Anak Usia 5 Tahun Berbasis Augmented Reality - Chrisdyanto, Daniel Nourman; Himamunanto, Agustinus Rudatyo; Sumihar, Yo’el Pieter (LPPM STIKOM Tunas Bangsa, 2024)
Introducing animals to early childhood is a crucial aspect of their initial educational development. At the age of 5, children are in a significant phase of developing language, observational skills, and conceptual understanding. In the context of learning, Augmented Reality (AR) can provide a more interactive and immersive learning experience compared to traditional methods. This application was created using Vuforia and Unity Engine, with the C# programming language. The application can display 3D animal objects, play animal sounds, and provide information about the animals in Indonesian. The animals featured in this application are the Brazilian turtle and the dog. Based on the data, images included in the Vuforia database showed a detection success rate of 7 out of 9 images for the Brazilian turtle. Meanwhile, for the dog, 10 out of 12 images included in the Vuforia database were successfully detected. These figures are reflected by the number of stars in the Vuforia database.